Uncovering In-Vitro Fertilization (IVF) Patient and Peer Relationships: A Qualitative Study on Self-Disclosure Processes in a Social Support Setting - Montgomery, Natalie Dimitra (Université d'Ottawa / University of Ottawa, 2021)
In Canada, the natural birth rate is declining in part because of delayed childbirth (Canada 2016). As a result of their decision to postpone parenthood and their increasing age, more couples are turning to assisted reproductive treatment (ART) including in-vitro fertilization (IVF) to conceive. The risk of IVF failure, the detrimental mental health outcomes (i.e. depression) associated with infertility, and the strain on physical, financial, spiritual, and emotional resources contribute to heightened stress for IVF patients, and compel them to identify and leverage psychosocial supports. Since the quality of social support individuals receive depends on the nature of communication they share with the receiver, it is important to consider how disclosure builds social support. Common social support channels such as spouses, family, friends, counsellors, and support groups and their associated communication patterns have already been explored in the fertility literature whereas processes integral to peer relationships, a support that women have signaled as promising, remain uncovered. It remains important to understand the nature of peer relationships in the context of infertility. This dissertation explores how in-vitro fertilization (IVF) users approached their decision to disclose to a peer and carried out their communication. Guided by the Disclosure-Decision Making Model (DD-MM) it starts by showing how IVF patients assess their support needs, and peers as recipients before communication takes place. It then delineates how these women execute their communication with specific focus on the modalities of their process and the scope of the disclosures of fertility-related and non-fertility related information between them. A sample population of 23 first-time and recurring IVF patients were interviewed. Results show that prior to disclosing to a peer, women reflect on information about their condition and their personal support needs on the basis of the adequacy of their social circles and perceptions of stigma, the benefits and drawbacks of secrecy versus transparency, and their personal motivation to leverage peer support. They also assess their peers, considering diverse pathways of connection as well as desirable peer traits which include IVF experience, other common ground and transparency. Relating to their communication, patients showed a distinct capacity to communicate with their peers and meet their support needs. The IVF patient-peer communication process is characterized through immediate disclosure transitions and backwards introductions, a solid mutual understanding when it comes to engagement and disengagement boundaries, a preference for digital communication via texting and instant messaging, and the coverage of a broad range of fertility topics in reciprocal conversations. The findings also show however that the majority of women choose to distance themselves and limit their conversations during the post embryo transfer waiting period and refrain from discussing pregnancy testing as a form of self- preservation. IVF patients share a natural relationship with peers. This dissertation points to opportunities to facilitate patient-peer relationships and enhance the fertility-care experience overall by embracing: the transparency of patients, better coping resources for men, safe places to personally connect in clinic and support group settings, and roles for all IVF patients in social support regardless of their outcome. It also suggests that patient-peer support is a pragmatic and flexible support channel that when managed properly can respond to patients’ personal disclosure and communication needs and preferences.
Keywords: Disclosure process; Peers; Infertility; Social support; Communication